Is Consciousness Necessary for Conflict Adaptation? A State of the Art - Desender, Kobe; Van Den Bussche, Eva (Frontiers in Human Neuroscience, 2012)
Facing response conflict, subjects try to improve their responses by reducing the influence of the detrimental information which caused the conflict. It was speculated that this adaptation to conflict can only occur when the conflicting information is consciously perceived. In this review we give an overview of the research looking at the possibility of unconscious stimuli to provoke this conflict adaptation. In a first part we discuss adaptation to conflict on a trial-by-trial basis. When the previous trial contained conflicting information, subjects will adapt to this by reducing the influence of the conflicting information on the current trial. However, the interesting question is whether this is also possible when the conflicting information remains unconscious. In a second part we will discuss blockwise adaptation to conflict. If conflict is very frequent, subjects will adapt to this by reducing the conflicting information sustainably. Again the question is whether this is possible when the conflict was never experienced consciously. In a third part we will discuss the neural basis of conscious and unconscious conflict adaptation. We will critically discuss the research on these topics and highlight strengths and weaknesses of the used paradigms. Finally, we will give some suggestions how future research can be more conclusive in this respect.